Acceptability of policies to reduce consumption of red and processed meat: A population-based survey experiment. (June 2022) - Pechey, Rachel; Reynolds, James P.; Cook, Brian; Marteau, Theresa M.; Jebb, Susan A.
Abstract: Policies to reduce meat consumption are needed to help achieve climate change targets, and could also improve population health. Public acceptability can affect the likelihood of policy implementation. This study estimated the acceptability of policies to reduce red and processed meat consumption, and whether acceptability differed when policies were framed as benefitting health or the environment. In an online experiment, 2215 UK adults rated the acceptability of six policies, presented in a randomised order. Prior to rating policies, participants were randomised to one of two framing conditions, with policy outcomes described either as benefitting health or the environment. Regression models examined differences in the primary outcome – policy acceptability (rated on a 7-point scale) – by framing. Labels were the most accepted policy (48% support), followed by a media campaign (45%), reduced availability (40%) and providing incentives (38%). Increasing price (27%) and banning advertising (26%) were the least accepted. A substantial proportion of participants neither supported nor opposed most policies (26–33%), although this fell to 16% for increasing price. There was no evidence that framing policy benefits from a health or environment perspective influenced acceptability (−0.06, 95%CIs: 0.18, 0.07). Fewer than half of the UK sample expressed support for any of six policies to reduce meat consumption, regardless of framing measures as benefitting health or the environment. Conversely, fewer than half expressed opposition, with the exception of price, suggesting considerable scope to influence public opinion in support of meat reduction measures to meet environmental and health goals. Highlights: Fewer than half this UK-representative sample supported meat reduction policies. Framing measures as benefitting health vs. the environment did not change support. Policies targeting meat were less supported than policies targeting unhealthy food. Many respondents had no decided views about the acceptability of policies on meat. There may be considerable scope to increase support for meat reduction policies.